The Comprehensive Analysis Of The Urinary Tract Infections In The Patients Admitted At The General Hospital In An-Najaf Province - Abed, Ahmed Salim; Mohammed, Eman Hamza; AL-Salami, Eman Hasani; Aldawmy, AL-Kadhem Khalaf (Medical Science Journal for Advance Research, 2024)
Background: Urinary tract infections (UTIs) are a pressing clinical problem for which relevant to microbial dynamics should be explored in-depth so to have better diagnostics, and treatment strategies for this group of infections. The paper deals complexity of UTI diagnosis containing multiple samples in which microbes were not found, therefore they did not meet the minimum bacterial concentration for diagnosis, thus “traditional” diagnostic paradigms no longer work. The hypothesis posits that this non-growth phenomena may point out the unknown causes instead of the bacterial infections, thus the need of the exploration of more advanced diagnostic protocols. Methods: Among 97 random urine samples of individuals admitted in a general hospital of Najaf city, Iraq, with April 2023 to October 2023 there was UTI. The diagnostic processes comprise of different tiers of clinical pathology tests, culture characteristics assessments and biochemical tests used in the study. Statistical analysis was carried out by using the GraphPad Prism computer software. Results: Microbiome analysis had shown presence of different micro-organismal communities, E. coli being the dominant bacterium for UTI, in conformity with established research propositions. Enlightening is that a three-sized group of samples show no detectable growth of pathogens, indicating the complexity of UTI identification. The plethora of Gram-negative microbes explained by the discovery of fungal isolates including Candida albicans, and the predominance of the less pathogenic strains demonstrate the importance of accuracy in therapeutic effort. Conclusion: This evidence shows the challenges in diagnosis and management of UTI in mouse, humanizing current assumptions. The discovery of "no growth" leads in turn to the need to explore the world of alternative causes for UTI symptoms, not excluding the non-bacterial nature of the latter.